The Ministry of Health, Welfare and Labor - His creation, functions and aspects offered - Paz Soldám, Carlos Emrique (1923)
At the recent regional legisladura Chincha whose sessions I was given chair, I had the honor to submit for the consideration of the legislative assembly the following draft message to the Executive asking for the creation of the Ministry of Health, Benefiicencia and Labour, whose initiative had distinguished by fellow physician Dr. Daniel Alfaro Street, regional deputy for Huancayo.